COMMENTS ON THE PROFESSIONAL VOCABULARY OF THE KAZAKH OF TOMDI DISTRICT - Kushkarbekova Marjona (Scholar Express Journal, 2023)
In this article, the attitude to linguistic issues and economic activities of Kazakh population of Tomdi district of Navoi region, specific aspects of their language, professional lexicon are expressed.
Keywords: linguistics; dialect; science; Kazakh